Stronger Together: Examining the Interaction Effects of Workplace Dignity and Workplace Inclusion on Employees’ Job Performance - Ahmed, Ammarah; Liang, Dapeng; Anjum, Muhammad Adeel; Durrani, Dilawar Khan (Frontiers in Psychology, 2022)
Despite growing interest in workplace dignity, there is a paucity of empirical research regarding whether and when it leads to higher job performance. To address these research gaps, this study examines the relationship between workplace dignity and job performance, identifying and examining the boundary condition role of workplace inclusion. Multi-source and time-lagged data were obtained from employee–supervisor dyads (n=169) in non-governmental organizations in Pakistan to test the hypothesized model, employing techniques such as confirmatory factor analysis, moderated multiple regression, post-hoc slope and Johnson-Neyman analyses. As predicted, workplace dignity and workplace inclusion positively influenced employees’ job performance, while workplace inclusion moderated the dignityperformance relationship such that this relationship was more strongly positive when workplace inclusion was high. At the theoretical level, this study adds new insights to the job-demands–resources (JD–R) model, which is used as theoretical lens in this study. Specifically, this study is the first to examine workplace dignity and its consequences from the perspective of the JD–R model, thus introducing a new theoretical perspective into the dignity literature. This study also provides useful advice for management practice, policy making, and employees, and is germane to the United Nations’ Sustainable Development Goal 8.